Energy and exergy analyses of a solar based hydrogen production and compression system - Ozcan, Hasan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, a solar thermal based integrated system with a supercritical-CO2 (sCO(2)) gas turbine (GT) cycle, a four-step Mg-Cl cycle and a five-stage hydrogen compression plant is developed, proposed for applications and analyzed thermodynamically. The solar data for the considered solar plant are taken for Greater Toronto Area (GTA) by considering both daily and yearly data. A molten salt storage is considered for the system in order to work without interruption when the sun is out. The power and heat from the solar and sCO(2)-GT subsystems are introduced to the Mg-Cl cycle to produce hydrogen at four consecutive steps. After the internal heat recovery is accomplished, the heating process at required temperature level is supplied by the heat exchanger of the solar plant. The hydrogen produced from the Mg-Cl cycle is compressed up to 700 bar by using a five-stage compression with intercooling and required compression power is compensated by the sCO(2)-GT cycle. The total energy and exergy inputs to the integrated system are found to be 1535 MW and 1454 MW, respectively, for a 1 kmol/s hydrogen producing plant. Both energy and exergy efficiencies of the overall system are calculated as 16.31% and 17.6%, respectively. When the energy and exergy loads of the receiver are taken into account as the main inputs, energy and exergy efficiencies become 25.1%, and 39.8%, respectively. The total exergy destruction within the system is found to be 1265 MW where the solar field contains almost 64% of the total irreversibility with a value of similar to 811 MW. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Mg-Cl cycle; Solar tower; Supercritical CO2; Energy; Exergy; HYBRID THERMOCHEMICAL CYCLE; MAGNESIUM-CHLORINE CYCLE; PERFORMANCE ASSESSMENT; OPTIMIZATION; STORAGE; DESIGN; POWER; Chemistry; Electrochemistry; Energy & Fuels